Serum Lipid Levels and Suicide Attempts Within 2 Weeks in Patients With Major Depressive Disorder: Is There a Relationship? - Zhou, Siyao; Zhao, Ke; Shi, Xiang; Sun, Huankun; Du, Siyu; Miao, Xuemeng; Chen, Jianjun; Yang, Fan; Xing, Minzhi; Ran, Wang; Lao, Jiaying; Zhang, Xiangyang; et al. (Frontiers in Psychiatry, 2021)
The potential correlation between serum lipid profiles and suicidal tendencies has been previously reported, however, it is unclear whether serum lipid profiles have definite relevance to recent attempted suicides in individuals suffering from major depressive disorder (MDD). Consequently, the relationship between blood lipids and suicide attempts in first-episode MDD patients in research was undertaken to verify. The cross-sectional study recruited overall 580 patients at the time of their first episode measuring up to diagnostic standard of MDD. Baseline demographic, clinical data and blood lipid level data were collected. Depression severity was measured with the Hamilton Depression Rating Scale (HAMD). Our results revealed that the level of TC may be identified as a promising and effective biomarker for first-episode MDD suicide risk, suggesting that screening of serum lipid profiles in depressive patients is essential for suicide prevention.